2019
DOI: 10.1111/nmo.13739
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rikkunshito on gastrointestinal symptoms and gastric motor function: The first study in a Belgian functional dyspepsia population

Abstract: Background: Rikkunshito, a traditional Kampo medicine, has shown efficacy to treat functional dyspepsia (FD) in controlled trials in Japan. Its putative benefit for European patients and mechanism of action has not been established.Methods: This study examined the effect of rikkunshito on gastric motility and GI symptom perception in FD-PDS patients in a randomized, placebo-controlled, crossover study. After a 2-week run-in period, patients received rikkunshito or matching placebo (2.5 g t.i.d.) for 4 weeks, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 35 publications
3
37
1
1
Order By: Relevance
“…Afterward, a second nasogastric feeding tube (Entral™, Maxtercatheters, Marseille, France) was inserted and positioned in the proximal stomach just below the LOS (not more than 5 cm below the LOS). [25][26][27][28][29][30][31][32][33][34] The position of both probes was confirmed by fluoroscopy. To ease intubation, Xylocaine ® 10% local anesthetic spray (NV AstraZeneca SA, Brussels, Belgium) and Endogel (TELIC, SA, Bigues, Spain) were applied.…”
Section: Intragastric Pressure Measurement With Highresolution Manometrymentioning
confidence: 68%
See 1 more Smart Citation
“…Afterward, a second nasogastric feeding tube (Entral™, Maxtercatheters, Marseille, France) was inserted and positioned in the proximal stomach just below the LOS (not more than 5 cm below the LOS). [25][26][27][28][29][30][31][32][33][34] The position of both probes was confirmed by fluoroscopy. To ease intubation, Xylocaine ® 10% local anesthetic spray (NV AstraZeneca SA, Brussels, Belgium) and Endogel (TELIC, SA, Bigues, Spain) were applied.…”
Section: Intragastric Pressure Measurement With Highresolution Manometrymentioning
confidence: 68%
“…For accurate data acquisition, the HRM probe was positioned in the fundus, corpus, and antrum following the larger curvature of the stomach. [25][26][27][28][29][30][31][32][33][34] The advancement of the tip of the probe into the duodenum is preferred but not essential for the assessment of fundus motility. Moreover, at least one sensor was placed at the level of the esophagus and at least once sensor at the level of the site of the lower esophageal sphincter (LOS).…”
Section: Intragastric Pressure Measurement With Highresolution Manometrymentioning
confidence: 99%
“…Shiratori et al used a barostat for measuring the volume of the stomach before and after the administration of rikkunshito in nine healthy volunteers and reported that the volume of the stomach increased significantly after the administration, with improvement in perceived stress ( Shiratori et al, 2011 ). Mausy et al examined the effect of rikkunshito on intra-gastric pressure with high-resolution manometry before and after treatment with rikkunshito; however, rikkunshito did not alter gastric motility ( Masuy et al, 2020 ). These differences might be caused by the characteristics of each modality.…”
Section: Discussionmentioning
confidence: 99%
“…Rikkunshito did not alter gastric motility. Treatment with rikkunshito improved upper gastrointestinal symptoms in FD patients, but similarly, high placebo effects were observed ( Masuy et al, 2020 ). A meta-analysis has reported that the combination of Western medication and rikkunshito was more helpful than the use of Western medication alone ( Ko et al, 2020 ).…”
Section: What Is Rikkunshito?mentioning
confidence: 97%
“…No adverse reaction for RKT was recorded in both studies. In recent years, there are six RKT RCTs for FD with close to 1000 FD patients involved 54–59 . One Japanese study reported that RKT significantly improved epigastric pain ( p = 0.04), especially in H. pylori ‐infected patients (RKT 40.0% vs. placebo: 20.5%, p = 0.07), and seemed less effective among H. pylori ‐uninfected participants 55 (RKT: 29.3% vs. placebo: 25.6%, p = 0.72), while another Japanese RCT showed non‐consumption of alcohol was associated with the efficacy of RKT especially among H. pylori ‐infected participants 56 .…”
Section: Potential Of Herbal Medicines In Fd—preclinical and Clinicalmentioning
confidence: 99%